The qualitative analysis of the composition of the RF discharge plasma by means of mass-spectrometry - Hladkovskiy, V.V.; Polozov, B.P.; Fedorovich, O.A. (Вопросы атомной науки и техники, 2016)
In this paper presents the research results of mass-spectroscopy of the RF discharge plasma in the
controlled magnetic fields. The discharge was conducted in the gases containing halogens and mixtures with the
oxygen. The evolution of the main plasma components from the oxygen content was investigated. Представлены результаты масс-спектрометрических исследований плазмы ВЧ-разряда в управляемых
магнитных полях. Разряд проводился в чистых галогенсодержащих газах и в смеси с кислородом.
Исследована эволюция основных компонентов плазмы от содержания кислорода. Представлено результати мас-спектрометричних досліджень плазми ВЧ-розряду в керованих магнітних
полях. Розряд проводився в чистих галогеновмісних газах і в суміші з киснем. Досліджено еволюцію
основних компонентів плазми від вмісту кисню.